Trends and Challenges of the Italian Third Sector in the Field of Community Assets Regeneration. New Convergences between Public Benefit and Social Entrepreneurship - Busacca, Maurizio; Zandonai, Flaviano (PARTECIPAZIONE E CONFLITTO, 2019)
The Paper investigates the challenges of the Italian Third Sector through the lens of their in-volvement in the management of community assets, such as when real estate and public spaces are re-generated on the purpose of activities of social interest, for instance confiscated properties to organized criminality, state-owned, religious corporations, and companies. Adopting the methodology of 'nested analysis', the paper explores quantitative data obtained from the ISTAT Census of non profit institutions, and qualitative data obtained from more than 50 case studies dealt with in recent scientific publications. Subsequently, the study further deepens the evidence emerged through the presentation and discussion of two case studies carried out by the authors: the Ex-Asilo Filangieri in Naples and Forte Marghera in Ven-ice. The Paper highlighted that actions of the Third Sector in the field of regeneration of community assets for social aims have not to be treated as nonprofit "industry", in which general trends towards publicness and entrepreneurship are very noticeable. On the contrary, it looks like a field in which new forms of the Third Sector are emerging, and we can sort them as "enterprising community".